Análisis jurídico de los derechos de la naturaleza como parte procesal conforme lo dispone el Artículo 30 del Código Orgánico General de Procesos. - Baño Andaluz Jhonder Jhonatan (2024)
This research aims to conduct a legal analysis of the rights of nature as a procedural party as provided for in Article 30 of the General Organic Code of Processes. This is important to examine because, as we all know, the conservation of nature is the cornerstone of sustainability on the planet, and each state has committed to protecting it through the recognition of the Sustainable Development Goals established by the United Nations. In current studies, the approach to nature as a subject of rights is still limited and focuses on specific aspects of foundation or criticism of novelty, without reaching constructive stages. For this reason, from the field of legal sciences, we have the obligation to seek explanations that are coherent with accumulated knowledge, while also contributing new insights that allow for the analysis of nature as a subject of rights. In the case of this research, it involves a study of the innovation of nature considered within the General Organic Code of Processes as a procedural party. It is clear that nature is represented within a process carried out by human beings, natural persons, legal entities, and social collectives. The trend is always to place greater emphasis on environmental damages that affect the rights or interests of humans, rather than on violations of the rights of nature when they do not have a direct influence on those rights. This can be observed both at the legislative level and in environmental studies, where nature generally remains an object rather than a subject of rights. Among the many obstacles to the adequate and effective protection of such rights of nature in judicial proceedings, these have been foreseen in the General Organic Code of Processes (COGEP). However, the question arises: Is there effectiveness in declaring nature as a procedural party, or from which perspective is this issue still being addressed as outlined in the preceding lines? 5 A qualitative approach will be used in this legal research, allowing me to collect, analyze, and interpret all relevant information for the development and support of the proposed topic. However, the research will also have a quantitative focus, as it will involve the collection of numerical data for subsequent analysis. The techniques to be used include interviews and surveys, and given that this is a legal research, the analysis of legal norms, bibliography, scientific articles, and documents will also be employed. I will conclude by analyzing the data obtained, comparing them with theory and law, to close the research with conclusions and recommendations. Keywords: Rights of Nature, Procedural Subject, Modernization of Law, Legality, Active Standing, Representativeness.